Research on Intelligent Monitoring and Early Warning of Electric Power Safety Based on Artificial Intelligence Technology. Issue 5 (January 2021) - Liu, Yu; Wang, Zuowei; Pan, Yingli; Zuo, Yue
Abstract: In recent years, with the continuous improvement of the national economic development level, the scale of urban construction in China is also gradually expanding. Therefore, since the monitoring system plays an important role in various industries, the establishment of an intelligent automatic management system can determine the unstable factors in the monitoring management and improve the safety performance of the monitoring system, so that the normal operation of the monitoring platform can be maintained. The establishment and function of the intelligent monitoring and early warning system are analyzed and studied in the paper, which combines traditional video monitoring equipment and data acquisition equipment into one, and launches a monitoring and early warning solution.